Resposta :
Olá,
Temos a integral:
[tex] \tt \int \: \dfrac{y}{y + 1} dy \\ [/tex]
Para resolver esta integral, vamos somar e subtrair 1 no numerador da fração:
[tex] \tt \int \: \frac{y + 1 - 1}{y + 1} \: dy \\ \\ \tt = \int \left( \frac{y + 1}{y + 1} - \frac{1}{y + 1} \right)dy \\ \\ \tt = \int \left( 1 - \frac{1}{y + 1} \right)dy \\ \\ \tt = \int \: 1dy - \int \: \frac{1}{y + 1} dy \\ \\ \tt = y - ln |y + 1| + k \\ [/tex]
Assim, temos que:
[tex] \boxed {\tt \int \: \dfrac{y}{y + 1} dy = y - ln |y + 1| + k}[/tex]